Musculoskeletal disorders among computer operators - Marzena Malińska (Nofer Institute of Occupational Medicine, 2019)
Work performed in a sitting position, despite the fact that it does not require a lot of physical effort, can be the cause of many musculoskeletal disorders (MSD), especially when performed for a long time and in the wrong position. Musculoskeletal disorders are currently a common problem in the working population. The article presents an analysis of selected literature on the occurrence of musculoskeletal disorders among computer operators. Particular attention was paid to the classification and reasons for the emergence of MSD. The latest reports on the occurrence of the disorders and the costs they generate, due to the inability to work and sick leaves, were also discussed. Med Pr. 2019;70(4):511-21